A critical realist approach to thematic analysis: producing causal explanations. Issue 4 (8th August 2022) - Fryer, Tom
ABSTRACT: Thematic analysis (TA) is one of the most popular methods in social science. There are several different approaches to TA that hold different ontological commitments, ranging from positivistic coding reliability TA to constructivist reflexive TA . However, there has been less focus on developing an approach that is informed by critical realism, with the notable exception of Wiltshire and Ronkainen. The first part of this paper proposes a five-step critical realist approach to TA. This approach aims to produce nuanced causal explanations of events, countering the mistaken assumption that qualitative research cannot produce causal knowledge. The second part of the paper brings this critical realist approach to TA into conversation with three alternatives: coding reliability, reflexive, and Wiltshire and Ronkainen's approach. The approach to TA in this paper builds on the strengths of these alternatives, offering an accessible way to adopt a critical realist philosophical grounding when doing TA.